2009
DOI: 10.1086/605721
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Methicillin-Resistant Staphylococcus aureus in a University Medical Center Day Care Facility

Abstract: There was a low prevalence of MRSA colonization in children and employees in the child care center but a higher prevalence of colonization in their families. Molecular typing showed that transmission of MRSA likely occurred in the child care center. The use of macrolide antibiotics and asthma medications may increase the risk of MRSA colonization in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
(4 reference statements)
0
15
1
Order By: Relevance
“…Importantly, our study which used molecular typing did not reveal evidence of person-to-person transmission of MRSA strains within classrooms. This is in contrast to the transmission observed by Hewlett et al in a single university-based facility (15). The molecular analysis of the colonizing MRSA strains revealed that six isolates were both PVL positive and SCCmec type IV, which is the classic molecular definition of CA-MRSA.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Importantly, our study which used molecular typing did not reveal evidence of person-to-person transmission of MRSA strains within classrooms. This is in contrast to the transmission observed by Hewlett et al in a single university-based facility (15). The molecular analysis of the colonizing MRSA strains revealed that six isolates were both PVL positive and SCCmec type IV, which is the classic molecular definition of CA-MRSA.…”
Section: Discussioncontrasting
confidence: 74%
“…Only limited information is available regarding the prevalence of colonization of healthy children attending CCCs in the United States. Single child care center prevalence studies have reported frequencies of MRSA colonization in children of 1.2% (2 of 164) (36) and 6.7% (7 of 104) (15). These results are similar to the 2.5% (3 of 122) (16) and 1.7% (5 of 291) (5) frequencies of MRSA colonization found in healthy children attending outpatient pediatric clinics in Chicago and to the 0.9% prevalence in children in Boston communities (24).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Further, patients with diabetes and inhaled corticosteroid exposure are immunosuppressed and at increased risk for colonization with MRSA. 25,26 Likewise, bronchiolar colonization and corticosteroid exposures are known risk factors for pneumonia due to Pseudomonas aeruginosa. 27 Many studies have identified prior antibiotic use as a risk factor for infections caused by MRSA and Pseudomonas aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…Community prevalence rates of MSSA and MRSA colonization vary depending on the population studied and the geographic region. Creech et al 10 MRSA colonization vary across studies but include minority race/ethnicity, 9,14 low socioeconomic status, 9,14 family member working in health care, 10,14 asthma medication use, 16 and exposure to antibiotics. 16 To our knowledge, this is one of the first studies to evaluate MRSA and MSSA colonization in otitis-prone children.…”
Section: Commentmentioning
confidence: 99%
“…Creech et al 10 MRSA colonization vary across studies but include minority race/ethnicity, 9,14 low socioeconomic status, 9,14 family member working in health care, 10,14 asthma medication use, 16 and exposure to antibiotics. 16 To our knowledge, this is one of the first studies to evaluate MRSA and MSSA colonization in otitis-prone children. Although not specifically evaluating for S aureus, Jacobs et al 19 20 Antibiotic exposure may also be a risk factor for colonization, and our patients received a mean of 3.7 antibiotic courses in the year before enrollment.…”
Section: Commentmentioning
confidence: 99%